NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM TRADISI KENDURI DI DESA TAMERAN KABUPATEN BENGKALIS - Riswanda, Muhammad Faiz; Putri, Nia Alfia; Rahayu, Putri (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
Tameran Village is one of the areas on Bengkalis Island which has a tradition that has been passed down from generation to generation and is still being preserved today, namely kenduri. This tradition is closely related to the community and is a culture that has experienced acculturation with Islamic religious teachings. The people of Tameran village believe that kenduri has an impact on human life. It seems as if the Kenduri tradition cannot be abandoned by the community, because if you don't carry it out, then most people feel like something is missing. Processions and equipment for the Kenduri tradition today also prioritize Islamic elements. This writing aims to examine in depth the implementation of the Kenduri tradition in the Tameran village community. as well as the values of Islamic religious education contained therein. The research method is descriptive qualitative with library research. The results of the research show that the festivities are carried out with various purposes, including spirit festivities, boyong festivities, akikah festivities, and so on. There are three series of processions in the kenduri, namely the opening, reading the prayer (core), and closing. The usual dishes at Tameran village festivities, namely tumpeng, ingkung, and apem are adapted to the purpose of the feast being held. The values of Islamic religious education contained in the Kenduri tradition are related to worship and monotheism to Allah SWT, giving alms by providing dishes, related to morals, namely human behavior that is in accordance with Islamic teachings, instilling friendship between people, mutual cooperation, and helping each other. Apart from that, kenduri is also a form of devotion and love for children to parents who have died. Kenduri is used as a means of strengthening community social relations